The Young Carthaginian: A Story of The Times of Hannibal - Henty, G. A. (George Alfred), 1832-1902 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Young Carthaginian: A Story of The Times of Hannibal" by G. A. Henty is a historical novel written in the late 19th century. The narrative centers on the struggles of Carthage during the tumultuous times of the Punic Wars, particularly focusing on the life and training of a young warrior named Malchus, the son of Hamilcar Barca. As Malchus navigates the complexities of war and politics, the story depicts themes of ambition, military prowess, and the crumbling political landscape of Carthage in comparison to the rising power of Rome. The opening of the book outlines a preface that reflects the author$1 (Bs intention to explore the events of the Punic Wars from a Carthaginian perspective. The narrator introduces a gathering of soldiers in the Libyan desert, detailing their weariness under the harsh sun and the diverse makeup of the Carthaginian forces, including Numidians and Iberians. The scene transitions into a characterization of Malchus, who, under the tutelage of his father, Hamilcar, is trained rigorously for the challenges ahead, positioning him as a capable protagonist. As the narrative unfolds, Malchus expresses eagerness for an impending lion hunt and shares discussions about the state of Carthage, hinting at the political unrest and challenges looming on the horizon, thus setting a dramatic backdrop for the story that is about to unfold. (This is an automatically generated summary.)s
Release date is 2004-02-01
Produced by Martin Robb, and David Widger
Keywords: Carthage (Extinct city) -- History -- Fiction; Rome -- History -- Republic, 265-30 B.C. -- Fiction; Hannibal, 247 B.C.-182 B.C. -- Fiction; Punic War, 2nd, 218-201 B.C. -- Fiction